Intervensi dan Dukungan terhadap Psikososial Sibling Anak dengan Penyakit Kronis - Hazrina Adelia; Nur Agustini; Dessie Wanda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine in a structured way the research results related to sibling interventions and support programs for children with chronic illnesses and their effects on psychosocial siblings. The method used is a systematic review using six electronic databases: Clinical Key Nursing, Scopus, Science Direct, Sage Journal Taylor & Francis, PubMed, and hand-searched. The keywords used to search for relevant articles in this study were: (sibling OR brother OR sister) AND (chronic OR disability) AND (Intervention OR therapy) AND (psychosocial OR psychology OR social). The results showed that as many as five articles were obtained discussing different types of intervention and support, which positively affected sibling psychosocial conditions. In conclusion, sibling intervention and support can be done through communication, the interaction between siblings, support groups, and art and nature therapy. Sibling intervention and support can positively improve the psychosocial condition of sibling children with chronic illnesses. Keywords: Support, Intervention, Chronic Disease, Siblings, Siblings